Climate Change Impact Assessment to the Proposed Coal Fired Power Plant Project at East Coast of Peninsular Malaysia - Samsuri, Rohmat; Kamal, Fauzan; Hayder, Gasim (International Journal of Engineering and Technology, 2018)
Tenaga Nasional Berhad (TNB) exploring possibility to build a coal-fired power plant at the East Coast of Peninsular Malaysia. With the growing awareness of potential challenges that may arise in the future power plants as a result of climate change, TNB has appointed a team which encompasses of Energy Ventures Division (EV), TNB and Tenaga Nasional Berhad Research (TNBR) to conduct Climate Change Impact Assessment to the Proposed Coal Fired Power Plant at the East Coast of Peninsular Malaysia. This study are to provide guideline on how climate change impacts assessment can be carried out, investigate potential climate change threats to be considered in the design of a coal-fired power plant. Potential sites siting for the proposed coal fired plant were assessed whilst literature review on global and local climate change prediction and projection was conducted.Â  Only 3 sites had fulfilled the criteria for a coal fired power plant which only 1 was selected as the Pilot Site (JG5) for this Study. The study had concluded that the climate change had significant impact to the proposed coal-fired power plant. The climate change threats are sea level rise, increase intensity of rainfall and extreme wind to the associated coal-fired power plant design i.e. coal import and handling facilities, shore and flood protection which based A1B scenario outlined in the SRES Storyline of AR4.